1996
DOI: 10.1046/j.1365-294x.1996.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPD analysis reveals low genetic variability in the endangered light‐footed clapper rail

Abstract: Numbers of light-footed clapper rails Rallus longirostris levipes, an endangered bird inhabiting southern California salt marshes, have substantially declined from historic levels. RAPD (randomly amplified polymorphic DNA) analysis was employed to assess the genetic variability within and among four of the largest remaining light-footed clapper rail populations. A single, larger population of the endangered Yuma clapper rail Rallus longirostris yumanensis was used for comparison. A total of 325 RAPD primers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Another unexpected result was the similar genetic composition of the Eastern and California Black Rail subspecies (Eddleman et al 1994), a pattern that has also been observed for other rail species (Fleischer et al 1995;Nusser et al 1996). Our result is particularly striking because similarity was observed not only for mtDNA, for which the subspecies shared one haplotype, but also for several microsatellites on which most alleles were common.…”
Section: Origins Of the Foothills Population And Phylogeography Of Thsupporting
confidence: 80%
“…Another unexpected result was the similar genetic composition of the Eastern and California Black Rail subspecies (Eddleman et al 1994), a pattern that has also been observed for other rail species (Fleischer et al 1995;Nusser et al 1996). Our result is particularly striking because similarity was observed not only for mtDNA, for which the subspecies shared one haplotype, but also for several microsatellites on which most alleles were common.…”
Section: Origins Of the Foothills Population And Phylogeography Of Thsupporting
confidence: 80%
“…To be effective, this fragment exclusion criterion should be applied at the population level (Lynch & Milligan 1994), and not to the overall fragment frequencies (e.g. Nusser et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Haig et al 1994;Nusser et al 1996;Antolin et al 2001), few studies to date have used RAPDs to analyze microgeographic genetic structuring (Apostol et al 1993;Masters & Forester 1995;Sinclair et al 1996). Although RAPDs are a common technique for comparing genetic differences among animal populations (e.g.…”
Section: Molecular Techniquesmentioning
confidence: 99%